The Relationship Between Mothers' Knowledge About Family Planning And Participation In Family Planning Programs - Cakrawati Cakrawati; Salsa Putri Aulia (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Family planning (FP) is one of the government's strategic programs to improve maternal and child health , regulate birth spacing , and enhance family welfare . Mothers ' participation in the family planning program is influenced by various factors , one of which is their level of knowledge regarding family planning . This study aimed to determine the relationship between mothers ' knowledge of family planning and their participation in the family planning program. This study employed a quantitative analytical design with a cross-sectional approach . The population consisted of women of reproductive age in the study area, and respondents were selected using a purposive sampling technique . Data were collected using a structured questionnaire and analyzed using univariate and bivariate analyses with the Chi- square test at a significance level of 0.05. The findings indicated that most respondents had good knowledge of family planning and actively participated in the family planning program. The Chi- square test showed a statistically significant relationship between mothers ' knowledge and participation in the family planning program (p < 0.05). It can be concluded that better knowledge is associated with higher participation in family Continuous planning​ health education and counseling is recommended to improve mothers ' knowledge and increase participation in the family planning program. Keywords : Knowledge , Mother , Family Planning , Participation , Contraception